Internalisai Nilai Pendidikan Damai dalam Membetuk Sikap Toleransi Ditengah Pluralisme Siswa - Muthoharoh, Miftakhul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
**Abstract** The diversity of Indonesia is a blessing granted by Almighty God. Therefore, this diversity should always be appreciated, nurtured, and developed by all elements, including educational institutions. Such efforts are necessary to foster a harmonious, peaceful, and tranquil life. Ironically, violence and conflicts among students based on differences continue to occur, sometimes leading to bullying. These behaviors often arise from a lack of education on the importance of tolerance in maintaining harmony amid diversity. SD Negeri 1 Balun is an example of a pluralistic school that successfully instills peaceful living and harmonious coexistence among students of different religions through peace education. This study aims to examine how SD Negeri 1 Balun internalizes peace education to foster student tolerance. A descriptive qualitative method is used in this research. The findings indicate that SD Negeri 1 Balun conducts peace education internalization, including respect, love, fairness, justice, cooperation, and tolerance in all school activities, from classroom lessons and extracurricular activities to habituation programs. As a result, tolerance naturally develops among students, enabling all SD Negeri 1 Balun students to live in harmony amidst their differences.